GIS untuk Pemetaan Keberadaan serta Analisis Keanekaragaman dan Dominansi Arthropoda Tanah di Lahan Pertanian Jagung : GIS for Mapping the Presence and Analyzing the Diversity and Dominance of Soil Arthropods in Maize Farms - Ardli Swardana; Bagus Irham Fathurohman; Dwi Rahayu Susanti (Research and Social Study Institute (RESSI), 2023)
Maize cultivation that are not environmentally friendly can disrupt the balance of the ecosystem, especially in the presence of soil arthropods. The aim of the study was to map the presence using GIS and calculate the diversity and dominance of soil arthropods on maize farms. The research was located in Banyuresmi District, Garut Regency, West Java, from June to August 2022. The research method used was spatial exploration, which selected 3 locations (A1, A2, and A3) maize farms and then installed pitfall traps. The next step was to identify, calculate the diversity index and dominance index of soil arthropods. The results revealed the presence of arthropods in A1 and A2, with 2 orders discovered, namely Hymenoptera and Coleoptera (A1) and Hymenoptera and Coleoptera (A2). But, 4 orders were found, namely Araneae, Hymenoptera, Orthoptera, and Dermaptera (A3). The diversity index values (A1 and A2) are in the low category, with consecutive values of 0.655 (A1) and 0.607 (A2), while in A3 is medium category with a value of 1.589. The dominance index in A1 is in the medium category with a value of 0.537, while A2 and A3 are the low category with consecutive values of 0.266 (A2) and 0.293 (A3).